Islamic Law and Local Tradition: Living Appasili Marriage in Takalar Regency Indonesia - Muh Zaitun Ardi; Nadyatul Hikmah Shuhufi (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2024)
The Appasili wedding tradition in Takalar Regency, South Sulawesi, has its uniqueness that is rarely found in other places. Appasili involves a series of distinctive rituals, such as marriage proposals, offerings, and joint celebrations, which show the importance of customs and rituals in the lives of the Takalar people. Each element in this tradition has a deep symbolic meaning, reflecting the cultural, spiritual, and social values ​​upheld in local society. The Appasili wedding process also highlights the important role of the extended family and community, showing solidarity and strong social integration in the celebration. This research aims to describe community perceptions and Islamic legal perspectives on this tradition. This research uses a qualitative approach and is field research with data collection techniques in the form of in-depth interviews with religious figures and traditional practitioners, as well as related documentation. The research results show that people view the Appasili tradition as a hereditary custom that is believed to perfect and cleanse a marriage. However, the impact is not uniform; Some traditional leaders believe that not carrying out Appasili will have a negative impact, while some people see it as a habit with no significant impact. From the perspective of Islamic law, the Appasili tradition is considered permissible (permissible) because it does not contain harm and is following the principle of